Ethical Research with Children - Richards, Sarah. author. aut Link
VIII, 185 p. 4 illus.
Keywords: An increasing interest in children's lives has tested the ethical and practical limits of research. Rather than making tricky ethical decisions, transparent researchers tend to gloss over stories that do not fit with sanitized narratives. This book aims to fill this gap by making explicit the lived experiences of research with children.